2006
DOI: 10.1116/1.2178386
|View full text |Cite
|
Sign up to set email alerts
|

Spiral twisting of fiber orientation inside bone lamellae

Abstract: The secondary osteon — a fundamental building block in compact bone — is a multilayered cylindrical structure of mineralized collagen fibrils arranged around a blood vessel. Functionally, the osteon must be adapted to the in vivo mechanical stresses in bone at the level of its microstructure. However, questions remain about the precise mechanism by which this is achieved. By application of scanning x-ray diffraction with a micron-sized synchrotron beam, along with measurements of local mineral crystallographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
185
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(205 citation statements)
references
References 30 publications
17
185
0
3
Order By: Relevance
“…However, to the best of our knowledge, stable crack propagation on the sub-osteonal / lamellar level, resolving bone micro-and nanostructure, has not been captured so far. Cantilever-based nanoindentation experiments revealed that these interlamellar areas are less stiff compared to lamellae, but stiffen selectively under This is in contrast with the lamellae, where the fibrils have been reported to be arranged in cholesteric layers with respect to osteon long axis (Wagermaier et al, 2006). Furthermore, a lower content of collagen and/or a higher content of NCPs is determined by means of μ-Raman imaging (Figure 4) on these areas.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, to the best of our knowledge, stable crack propagation on the sub-osteonal / lamellar level, resolving bone micro-and nanostructure, has not been captured so far. Cantilever-based nanoindentation experiments revealed that these interlamellar areas are less stiff compared to lamellae, but stiffen selectively under This is in contrast with the lamellae, where the fibrils have been reported to be arranged in cholesteric layers with respect to osteon long axis (Wagermaier et al, 2006). Furthermore, a lower content of collagen and/or a higher content of NCPs is determined by means of μ-Raman imaging (Figure 4) on these areas.…”
Section: Discussionmentioning
confidence: 97%
“…Further concentric arrangement of cylindrical lamellae results in a hollow cylindrical laminate structure, known as an osteon, which surrounds a blood vessel (Fratzl and Weinkamer, 2007). In a single osteonal lamellae, the previous mentioned sub-layers rotate to an angle from roughly 10° to 60° in respect to osteon long axis (Wagermaier et al, 2006). Finally, between two subsequent lamellae lies a putatively NCP-rich (Derkx et al, 1998) interlamellar area where the mineralized collagen fibrils are oriented perpendicularly to the longitudinal axis of the osteon (Ascenzi and Benvenuti, 1986;Reid, 1986;Ziv et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations have been made with respect to the periodic region of the dactyl club and helicoidal structures found within most arthropod cuticles as well as other Submitted to 8 natural composite materials including lamellar bone, cell walls of wood and fish scales. [17,18,[28][29][30][31][32][33] Crack deflection is an extrinsic form of toughening that is well-documented in natural composite materials, specifically biomineralized tissues. [3] The periodic nature of hard and soft interfaces, in this case between alpha-chitin fibrils and hydroxyapatite crystals, results in a crack-tip shielding effect that changes the crack driving force and thereby arresting crack propagation.…”
Section: A Sinusoidally-architected Helicoidal Biocompositementioning
confidence: 99%
“…Neighboring layers are rotated with respect to each other, resulting in a nearly isotropic distribution of fibril directions when averaged over the entire thickness of the cell wall. Plywood architectures are very common as strategies for reinforcement of plants [11][12][13], bone [11,[14][15][16], collagen [17], and chitin [18,19]. Although consisting only of dead tissue, wheat awns work like muscles, being able to transport seeds away from their host.…”
Section: Introductionmentioning
confidence: 99%